1996
DOI: 10.3354/meps141083
|View full text |Cite
|
Sign up to set email alerts
|

Biokinetics of selected heavy metals and radionuclides in the common Mediterranean echinoid Paracentrotus lividus: sea water and food exposures

Abstract: Uptake and loss kinetics of Zn, Ag, Cd, '=CS, and 241Am by the echinoid Paracentrotus lividus contaminated through either water or food were determined in controlled laboratory radiotracer experiments using low contaminant concentrations. The echinoid efficiently accumulated most of the elements from water. The only exception was '"CS (concentration factor at steady state = 2.71. With respect to relative metal bioavailability, concentrations in the different body compartments of P lividus were generally ranked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
95
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(105 citation statements)
references
References 27 publications
(36 reference statements)
4
95
0
Order By: Relevance
“…Rapid turnover of radiocesium was also found in many bivalve species (Bryan 1963, Harrison 1972, Cranmore & Harrison 1975. Similarly, Warnau et al (1996) reported that the depuration rate constant of radiocesium in the echinoid Paracentrotus lividus was 0.116 d -1…”
Section: Discussionmentioning
confidence: 86%
“…Rapid turnover of radiocesium was also found in many bivalve species (Bryan 1963, Harrison 1972, Cranmore & Harrison 1975. Similarly, Warnau et al (1996) reported that the depuration rate constant of radiocesium in the echinoid Paracentrotus lividus was 0.116 d -1…”
Section: Discussionmentioning
confidence: 86%
“…In other invertebrates such as echinoderms or bivalves, the major fraction of the radiotracers was found in the calcified parts, i.e. the body wall of sea urchins (Warnau et al 1996) and the shell of mussels . Although the cuttlefish Sepia officinalis has a calcareous compartment (the cuttlebone) representing ca.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most marine invertebrates, which accumulate Cd mainly from seawater (Dahlgaard 1981, Nolan & Dahlgaard 1991, Warnau et al 1996, cephalopods such as Sepia officinalis accumulate Cd principally from food. Once incorporated, the fate of this metal is mainly controlled by the digestive gland, which acts as an efficient detoxification organ whatever the source of Cd (seawater, food, or sediment).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…counted in 150 ml of seawater) before and after each water renewal in order to determine the time-integrated radiotracer activities, i.e. the mean value of all measurements performed over the time period considered (Warnau et al, 1996). At different time intervals, the three radionuclide activities were counted in 3 dissected eggs (γ -emitters could be detected in the same sample according their γ -emissions energy) to determine the radiotracer distribution between the eggshell and vitellus or among eggshell, vitellus, embryo and peri-vitelline fluid, i.e.…”
Section: Organisms Radiotracer and Experimental Proceduresmentioning
confidence: 99%